2006
DOI: 10.2176/nmc.46.147
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Meningioma With Large Cyst-Case Report-

Abstract: A 29-year-old male presented with loss of consciousness and generalized seizure, followed by right hemiparesis and speech disturbance. Computed tomography and magnetic resonance imaging showed a solid, enhanced tumor with a cyst in the left frontal area with surrounding edema and mild mass effect. The cyst wall was also enhanced. The preoperative diagnosis was cystic falx meningioma. The tumor was totally resected, but most of the cyst wall adhered tightly to the surrounding brain and could not be removed. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…This suggests that the presence of cyst may not affect the extent of meningioma resection. The presence of cyst is believed to be re ective of higher grade meningioma [12,34,35,21]. Analogous to Weber et al [29], we noted that most cystic meningiomas were WHO grade I and had low Ki-67/MIB proliferation index.…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that the presence of cyst may not affect the extent of meningioma resection. The presence of cyst is believed to be re ective of higher grade meningioma [12,34,35,21]. Analogous to Weber et al [29], we noted that most cystic meningiomas were WHO grade I and had low Ki-67/MIB proliferation index.…”
Section: Discussionsupporting
confidence: 82%
“…4,8 Many etiologies have been suggested for cyst formation in meningiomas, which may represent rapid growth or aggressive behavior of tumor cells, including cystic degeneration, direct secretion of fluid by tumor cells, ischemic necrosis and absorption of hemorrhage within the tumors. 4,10,11 Our study showed that intratumoral cystic change was significantly more frequent in grade II/III meningiomas (43.8%) than in grade I meningiomas (6.8%) (p = 0.001).…”
Section: Discussionmentioning
confidence: 62%
“…9,19 The frequency of atypical meningioma among cystic meningioma is 12%, higher than that among all meningiomas, and suggests that atypical meningioma tends to form a cyst compared with other subtypes. 20 Review of the histological classification of 69 cystic meningiomas showed meningotheliomatous (42.0%) and fibroblastic (27.5%) lesions were the most common types. Lesions were malignant in 7.2% of cases.…”
Section: Discussionmentioning
confidence: 99%